Mille quatre-vingts bougies - Véronique Gruca (Ateliers d'Anthropologie)
This article presents a Buryat shamanic ritual observed in July 2015 in north-eastern Mongolia, in the village of Bayan-Uul (Dornod region). During the buyan ritual, the participants “make merits” in the name of two deceased persons with the intention of successfully reincarnating both souls. This article offers an analysis of the ritual, focusing on interactions and on the participants’ placement in time and space, highlighting the reconfigurations of relations between the participants. This approach shows how the shaman positions herself as a mediator within the ritual and manages to establish communication between the living and the dead. This particular form of mediation with the invisible highlights the intrinsically ambiguous nature of Mongolians’ relations with the dead.